Establishing the influence of milking systems in cows during milking - Палій, А. П. (Scientific Progress & Innovations, 2016)
In-depth knowledge of the laws of basic physiological functions of the body lactating cows is a highly powerful tool to stimulate milk production and, thus, to increase the use of the genetic potential of animals. Adequate and effective milking of cows of high performance is to use the most appropriate physiological reactions, underlying the formation of milk and milkgiving. In designing and evaluating of the system gentle milking of cows need to consider the impact on the teats of the udder cows are not only characteristics such as milk yield of dairy cattle, the contents of somatic cells in milk, milk flow dynamics, peak milk flow rate and milking time, but also pay attention to the state of the teats of the udder with taking into account their relationship with the other characters. Prompt identification and elimination of the factors, that negatively affect the organism of animals during milking, is a prerequisite to ensure effective use of dairy cattle.